The projects of governors on transformation of the Volost justice: about the creation of universal local court - Popp, Ivan; Zinnatullina, Zulhya (Przegląd Wschodnioeuropejski, 2019)
The article is devoted to the poorly studied problem of creating in 1860–1880’s. a single, local, elected local court in the Russian Empire, which could best respond to the needs of socio-economic development of the country. It was very important after the Emancipation Reform of 1861 in Russia. As the main source the authors use 30 projects of Governors prepared for the Special Commission, which worked on creating the project of local government. These projects can be divided into two groups and each of them had its advantages and disadvantages. In 1885 the Special Commission created the project of new court, but which was not realized.